Association between serum uric acid level and microalbuminuria among type 2 diabetic patients: a cross-sectional study - Mumtaz , Ahmed; Hadi Hasan, Abdul; Hassan, Ramsha; Hassan, Muhammad; Khan, Tayyab Mumtaz; Warrarich, Bismah Imtiaz; Tauqeer, Alizay; Fatima, Syeda Ammara; Amer, Marryam; Akram, Jehanzeb (International Journal Of Community Medicine And Public Health, 2023)
Background: Diabetic nephropathy is common and its advancement is affected by different factors and one of them, serum uric acid has crucial role in the progression of kidney injury. The objective of this study is the determination of the association of serum uric acid level with the microalbuminuria among type 2 diabetic patients. Methods: This cross-sectional study was performed in a tertiary care hospital of Rawalpindi, among 108 patients for 8 months from March 2021 to October 2021. Patients’ recruitment was done by the inclusion and exclusion criteria and convenient sampling technique. Data was obtained via a self-designed proforma. Descriptive and inferential statistics were applied for data analysis. P<0.05 was taken as statistically significant Data analysis was performed by SPSS version 25.0. Results: From total study population, 60 (55.55%) were females, whereas, 48 (44.45%) were males. The means of age for the study population and serum uric acid were 48.98±15.67 years and 7.12±0.91 respectively. The overall frequencies of hyperuricemia and microalbuminuria were 41 (37.96%) and 33 (30.55%) respectively. The frequency of hyperuricemia was higher among older age group, women, and patients with microalbuminuria. The associations of serum uric acid level with the age group, gender, and albuminuria were significant statistically. Conclusions: Correlation between the serum uric acid levels and albuminuria is statistically significant. Serum uric acid levels have statistically significant relationship with age and gender as well. Serum uric acid level was higher among older age group, females, and patients with microalbuminuria.